Victimological Review Of The Criminal Offence Of Child Abuse By Father And Step-Uncle - Rizal Alulu; Lisnawaty W. Badu; Mohamad Taufiq Zulfikar Sarson (Universitas Negeri Gorontalo, 2023)
Abstract: This study aims to determine the victimology review of victims of criminal acts of child molestation committed by their stepfather and uncle. This research raises two issues, namely how to review the victimology of victims of criminal acts of sexual abuse and the form of legal protection for children who are victims of criminal acts of sexual abuse. This research uses empirical legal research methods with a descriptive approach. The results of this research show that children who are victims of criminal acts of sexual abuse have a passive role in that they do not act, but with their attitude they push themselves to become victims, resulting in crimes occurring against them, whose nature and character tend to be weak physically and in terms of their thinking power. The legal protection provided is contained in Law Number 35 of 2014 in place of Law Number 23 of 2002 concerning Child Protection. Protection efforts include the rehabilitation of children who are victims and providing protection for the broadcast of victims' identities to prevent labeling of children which affects the future of children who are victims of criminal acts of sexual abuse.